Extraction of lemon oil from citrus limon peels via ultrasonic assisted extraction - Dhanakumar, Suppiah (2008)
Ultrasound-assisted extraction was evaluated as a simpler and more effective alternative to conventional extraction methods for the isolation of lemon oil from peels of Citrus limon. The samples were extracted with different solvents, under indirect sonication in an ultrasound cleaning bath. The ultrasonic extraction was not only more efficient but also convenient for the recovery and purification of the active ingredients of plant materials. In addition, the sonication-assisted extraction can be carried out at lower temperatures which are favorable for the thermally unstable compounds. It is found that the ·optimum yield was achieved by diethyl ether with extraction time of 30 ·minutes compare to dichloromethane and n-hexane. Oil extracted with n-hexane has highest quality as the amount of limonene in oil high.